Climate Risk Management in Agricultural Extension – Kenya Handbook - Hansen, J; Dinku, T; Grossi, A; Huyer, S; Moore, M; Dinh, D; Ruirie, O; Okach, L; Kiambe, K; Ngesa, J; Mungau, L; Nganga, I; et al. (2025)
Improvements in the weather and climate information available in Kenya provide new opportunities for agricultural extension personnel to help farmers better manage the risks that they face, and to adapt recommended technology packages to local climatic conditions. This 2-week course aims to equip agricultural extension workers to access, understand and incorporate climate information into their professional work. It is designed to provide foundational knowledge on climate and agricultural decision making; and practical tools to analyze climate-related risks, use appropriate weather and climate information to support agricultural decisions, communicate complex climate information effectively with farmers, and integrate climate services into agricultural extension activities. This course is designed for public and private agricultural extension professionals who actively support farmers with information, advice and other services. It targets extension agents working at the ward, sub-county and county levels within Kenya’s public sector agricultural extension service, and non-government extension and advisory service professionals with a comparable background. The training course includes sessions covering climate risks in agriculture, digital innovations, and strategies like climate-smart agriculture and ecosystem-based adaptation. Course activities require basic computer literacy; and include interactive lectures, group discussions, self-assessments, case studies and hands-on tool demonstrations. Participants can use this Handbook resource to guide engagements such as role-playing, community engagements, and awareness campaigns.